Analisis Perbandingan Kualitas Pelayanan Pada Roxy Market Dan Victory Market Kabupaten Alor - Famaney, Loisa Paulina; Awang, Mesak Y.; Anigomang, Ferdinand Romelus; Maruli, Elia (Peneliti.net, 2023)
Service quality is the service provided by employees to buyers at Roxy Market and buyers at Viktory Market on a measure of how good the level of service provided is in accordance with customer expectations or expectations. This study aims to determine the comparison of service quality at Roxy Market and Victoy Market, Alor Regency. This type of research is quantitative research with data collection techniques, namely observation, interviews, questionnaires studies. This research uses primary data. The population in this study were buyers at Roxy Market and Victory Market in Alor Regency and the sampling technique in this study was accidental sampling. Accidental sampling is a sampling technique based on coincidence, that is, anyone who happens to meet the researcher can be used as a sample, if it is deemed that the person met by chance is suitable as a data source. So the respondents in this study were 31 respondents who shopped at Roxy Market and Victory Market, Alor Regency. The statistical method used in this study is descriptive statistical analysis and t-difference analysis by looking at the significant value as a yardstick in talking the hypothesis. The results of this study indicate that (1). The level of achievement of respondents in service quality at Roxy Market is 90.50% with a very good weighting category. So the results of this study received H1 which states that the service quality variable at Roxy Market is in the very good category (2). The service quality variable at Victory Market with the achievement level 85.71% of respondents with very good weighting category so that the results of the study received H2 which stated that Victory Market was in the very good break-in category (3) service quality variable at Roxy Market which had the highest respondent achievement rate, namely 90.50% with very good weighting category H3 which states that the service quality variable at Roxy Market is in the very good category (4). By looking at the significant value of the t test on 2 parties, namely for the service quality variable at Roxy Market and sevice quality variable at Victory Market of 0.038 <0.05 or 5% so that the results of the study can be concluded that there are differences in service quality at Roxy Market and service quality variables at Victory Market. H4 which states that there are differences in service quality at Roxy Market and service quality variables at Victory Market